Escritura e imagen en Yves Bonnefoy. Una aproximación desde la historia del arte - Sánchez Ramón, Mar (Escritura e Imagen, 2005)
The writings about art and the artists of Yves Bonnefoy are a convergence point between the art critic and art history. They contribute to a method of approach to the art object from a humanist perspective. He uses referential, personal and psychological analysis, but without being absolutely away from the scientific method. It is based on a search for truth using a precise language, with specific terms, as each science has. These terms have been assembled for the first time in my Glossary about the art writings of Yves Bonnefoy which is part of my University Dissertation. Yves Bonnefoy’s work opens important perspectives for art history. They show us new ways to bring near and to extend our knowledge of the artists and their artistic creations.